2014
DOI: 10.1016/s0968-8080(15)43824-8
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of first trimester medical abortion in Armenia

Abstract: In Armenia, abortion is the main means of fertility regulation; however, before research activities were initiated only surgical methods were available and the quality of services was low in some areas. Our clinical study from 2008-2011 aimed to show that early medical abortion is an acceptable and feasible option. A total of 700 eligible women with pregnancies up to 63 days LMP presenting for abortion were recruited for the study in five locations. Participants took 200 mg mifepristone and 800 μg buccal misop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Lastly, the option to take both medications at home did not create undue burden for providers, as evidenced in the few phone calls and unplanned visits to the clinic. Numerous studies support these findings, and home mifepristone and misoprostol is regularly offered to women in Moldova, Georgia, Azerbaijan, and Armenia [7,9,10,20].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lastly, the option to take both medications at home did not create undue burden for providers, as evidenced in the few phone calls and unplanned visits to the clinic. Numerous studies support these findings, and home mifepristone and misoprostol is regularly offered to women in Moldova, Georgia, Azerbaijan, and Armenia [7,9,10,20].…”
Section: Discussionmentioning
confidence: 87%
“…Many clinical care guidelines, including the WHO 2012 safe abortion guidance [1], recommend outpatient medical abortion up to 63 days since the last menstrual period (LMP), including taking misoprostol at home to maximize the convenience and acceptability of the service. Recent evidence shows that medical abortion is safe, effective, and acceptable as an outpatient service up to 70 days after the LMP [2–6], and the option to take both mifepristone and misoprostol at home is safe and desired by a substantial proportion of women [7–11]. In some countries—e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Success and complication rates were not different between home users and clinic users [4][5][6][7][8]. Success and complication rates were not different between home users and clinic users [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, research studies in settings as varied as Armenia, Azerbaijan, Nepal, the US and Kazakhstan have demonstrated that the outside-office-use option is popular and acceptable among women [6][7][8][9][10]. The proportion of women choosing to take the mifepristone at home ranged from 46%-74%, and among these users, 92%-99% would choose to take it out of the office again for a future abortion (Fig.…”
mentioning
confidence: 99%